2013
DOI: 10.1515/jpm-2012-0256
|View full text |Cite
|
Sign up to set email alerts
|

Is 5-methyltetrahydrofolate an alternative to folic acid for the prevention of neural tube defects?

Abstract: Women have higher requirements for folate during pregnancy. An optimal folate status must be achieved before conception and in the first trimester when the neural tube closes. Low maternal folate status is causally related to neural tube defects (NTDs). Many NTDs can be prevented by increasing maternal folate intake in the preconceptional period. Dietary folate is protective, but recommending increasing folate intake is ineffective on a population level particularly during periods of high demands. This is beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 134 publications
(199 reference statements)
3
59
0
4
Order By: Relevance
“…Associations tended to be weaker in pregnant and lactating women. The biologically active derivate [6S]-5-methyltetrahydrofolate ([6S]-5-MTHF) has been found to be more effective than folic acid supplementation in improving folate status [49], and since it represents the main folate form in cord blood (mean 89.4% of total folate), it may be hypothesized that 5-MTHF can provide an immediate source for folate to be transported to the fetus [50]. …”
Section: Folatementioning
confidence: 99%
“…Associations tended to be weaker in pregnant and lactating women. The biologically active derivate [6S]-5-methyltetrahydrofolate ([6S]-5-MTHF) has been found to be more effective than folic acid supplementation in improving folate status [49], and since it represents the main folate form in cord blood (mean 89.4% of total folate), it may be hypothesized that 5-MTHF can provide an immediate source for folate to be transported to the fetus [50]. …”
Section: Folatementioning
confidence: 99%
“…Additional scientific evidence could also refine and improve the undisputed effectiveness of folic acid supplementation. Issues for research include the characterization of effects on CA other than neural tube defects [38,39], the 5-methyl-tetrahydrofolate as possible alternative to folic acid [40] and the mechanisms (immune factors, inositol metabolism) and risk factors of the neural tube defects that are resistant to folic acid supplementation [41,42]. Most importantly, folic acid is also an issue for public health research, e.g., strategies to promote a community awareness on periconceptional supplementation [43] and a robust and consistent definition of recommended intake levels for folates [44].…”
Section: Tablementioning
confidence: 99%
“…FA fortification of the food couldn't archive optimal folate level in the plasma. So, supplementation in preconceptional period at the moment is the best way to improve the folate status within a relatively short time (4-12 weeks) [13]. The use of MVs containing FA and other B vitamins in several studies showed high efficacy in the reduction of NTDs (about 90%), then the use of high or low dose of FA alone.…”
mentioning
confidence: 99%
“…Although there are no clinical trials on the effectiveness of 5-MTHF in preventing NTDs, metabolic studies have shown that 5-MTHF is a biologically active form of the vitamin and it seems to be at least as effective as FA in improving folate biomarkers. The literature clearly shows that a better food folate intake is associated with better folate markers and that food folate can prevent NTDs (by increasing folate status) [6,[13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation